Controlled Synthesis of Self-Assembled CdS Hierarchical Microspheres Through a Mixed-Solvothermal Route - Deng, Chonghai; Hu, Hanmei; Du, Peng; Han, Chengliang; Tian, Changan; Yang, Benhong (Asian Journal of Chemistry, 2012)
Three kinds of hierarchical three-dimensional (3D) hexagonal CdS microspheres with different building blocks (nanoparticle-based microspheres, nanosheet-based microspheres and nanorodbased microspheres) were fabricated using CdCl2·2.5H2O and NH2CSNH2 as starting materials through a facile mixed-solvothermal route. Various techniques have been used to characterize the prepared products, such as XRD, FESEM, TEM and UV-visible absorption spectroscopy. The experimental results indicated that the morphologies of CdS microcrystals were greatly affected by the volume ratio of two different solvent. When the volume ratio of ethylenediamine and ethanol were changed from 2:1, through 1:1 to 1:2, the building units of CdS microspheres could be changed from nanoparticles, through nanosheets to nanorods. UV-Vis absorption spectra confirmed that as-obtained three kinds of microspheres all have obvious quantum-confinement effect.